Extraskeletal osteosarcoma and its histological mimics - Leonard N. Yenwongfai; Jinpeng Liu; Chi Wang; Therese J. Bocklage (Elsevier, 2022)
Extraskeletal osteosarcoma (EOS) is a sarcoma primary to soft tissue that produces tumor osteoid or bone (mineralized osteoid). It is rare, occurs generally in middle-aged to older adults in the extremities, and typically is histologically high grade. There are no diagnostically helpful findings of EOS prior to biopsy, as the clinical presentation is non-specific, and imaging studies may not demonstrate mineralization. Core needle biopsies may fail to sample neoplastic osteoid/bone, rendering specific diagnosis on these small tissue specimens challenging. Even if a core biopsy yields osteoid, the diagnosis is not straightforward, as the histologic differential diagnosis of EOS is broad. Other sarcomas primary to soft tissue may occasionally produce bone or osteoid, such as dedifferentiated liposarcoma and synovial sarcoma, among others, thereby mimicking EOS. Depending on the body site involved, such as superficial location in the head and neck, non-mesenchymal tumors also enter the differential such as sarcomatoid carcinoma. To further complicate diagnostic evaluation, certain benign mesenchymal tumors that form reactive, hypercellular osteoid/bone may be mistaken for extraskeletal osteosarcoma such as myositis ossificans. Thus, correct diagnosis of EOS requires excluding these other malignant and even benign entities that contain tumoral osteoid and/or hypercellular reactive bone. Ancillary testing, including immunohistochemistry and molecular genetic analysis, may be necessary to reach the correct diagnosis.